Fates of potassium during co-pyrolysis of corn stalk and plastic film components - Chao Fan; Jing Liu; Junxia Wang; Jian Li; Zixi Han; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Biomass and Bioenergy, 2027)

Mutually reinforcing removal of uranium(VI) and nitrate enabled by pH-buffered nitrogen-doped carbon nanotube-calcium phosphate derived from corn stover and mussel shells - Jun Hu; Weidong Cheng; Yidan Zhang; Jian Ni; Junxia Yin; Wentao Zeng; Yuling Zhu (Bioresource Technology, 2026)

MH-induced co-carbonization of medium–low temperature coal tar pitch for fine-grained mosaic coke and its supercapacitor application - Shuaichao Song; Jianfeng Deng; Junxia Cheng; Wei Guan; Xiliang Wen; Yaming Zhu; Xuefei Zhao (Fuel, 2026)

Nitrogen-doped activated carbon derived from medium-low-temperature coal tar pitch and recovered quinoline for phenol adsorption - Jianfeng Deng; Huichao Zhang; Jiao Huang; Bingjian Zhao; Li Yue; Junxia Cheng; Xuefei Zhao; Yaming Zhu (Journal of Environmental Chemical Engineering, 2026)

Preparation Strategies and Application Progress of Coal-Based Carbon Dots - Zishuo Gu; Wei Zhao; Shuang Pang; Chaoshuai Hu; Junxia Cheng; Xuefei Zhao; Yaming Zhu (Journal of Fluorescence, 2026)

Analysis of the “South-High North-Low” phenomenon of aerosol distribution and its characteristics in the Beijing plain area - Jie Su; Ju Li; Jingjiang Zhang; Junxia Dou; Youjun Dou; Shaoying Shi; Yaoting Wang; Yao Wang; Zhigang Cheng; Wenlong Zhang (Atmospheric Pollution Research, 2026)

Study on the air oxidative modification and coking behavior of medium- and Low-Temperature coal tar pitch - Jianfeng Deng; Jiaxing Yue; Yaming Zhu; Yuzhu Zhang; Junxia Cheng; Xuefei Zhao (Fuel, 2026)

Simultaneous remediation and fertilization of saline-alkaline soil via the application of various phosphorus-rich hydrochars - Ran Duan; Yuxin Yang; Xuchen Zhang; Junxia Wang; Jipeng Luo; Xiaoqiang Cui; Zhanjun Cheng; Guanyi Chen (Chemical Engineering Journal, 2026)

Functionalization and regeneration mechanisms of waste-derived ultrafine green coke-based spherical activated carbons: Transforming high-performance cationic/anionic dye adsorbents into supercapacitor electrodes - Jiao Huang; Yaming Zhu; Jiaxing Yue; Yuzhu Zhang; Junxia Cheng; Xuefei Zhao (Chemical Engineering Journal, 2025)

Insight into the transformation of phosphorus in soil affected by microplastics: A review - Xuchen Zhang; Shicheng Dong; Junxia Wang; Kiran Yasmin Khan; Zhanjun Cheng; Xiaoqiang Cui; Jipeng Luo; Beibei Yan; Guanyi Chen (Environmental Research, 2025)

Evolution of phosphorus during co-pyrolysis of wheat straw and mulch film components - Chao Fan; Junxia Wang; Yuxin Yang; Jian Li; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Chemical Engineering Journal, 2025)

Preparation of high specific surface area porous carbon from waste bamboo fiber for high performance supercapacitors - Fei Wang; Zixian Jia; Yaming Zhu; Tongtong Zhang; Junxia Cheng; Xuefei Zhao (Biomass and Bioenergy, 2025)

Dual-functional oxygen-modified pitch-based spherical activated carbon enhanced VOCs capture: Experiment-simulation integration - Xiliang Wen; Ziyang Su; Junxia Cheng; Shuaichao Song; Wei Guan; Pengfei Cheng; Yaming Zhu; Xuefei Zhao (Journal of Environmental Chemical Engineering, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

Study on the characterization and thermal conversion behavior of sequential extraction products from medium temperature coal pitch - Jiaxing Yue; Huimei Liu; Yaming Zhu; Yunliang Xu; Chaoshuai Hu; Junxia Cheng; Yonghui Bai; Xuefei Zhao (Fuel, 2024)

Molten salt-assisted carbonized zeolite imidazolate framework on nickel foam for highly efficient iodide capture in fluoride molten salts - Ming Cheng; Junxia Geng; Yujiao Wang; Qin Lin; Xiaoyu Zhang; Lixin Sun; Qiang Dou; Haiying Fu (Chemical Engineering Journal, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

Activation of ephrinb1/EPHB2/MAP-2/NMDAR Mediates Hippocampal Neurogenesis Promoted by Transcranial Direct Current Stimulation in Cerebral-Ischemic Mice - Xiaojiao Ma; Oumei Cheng; Qingsong Jiang; Junxia Yang; Huan Xiao; Hongmei Qiu (NeuroMolecular Medicine, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Assessing the Influence of Aerosol on Radiation and Its Roles in Planetary Boundary Layer Development - Zhigang Cheng; Yubing Pan; Ju Li; Xingcan Jia; Xinyu Zhang; Pengkun Ma; Qianqian Wang; Junxia Dou; Jingjiang Zhang; Jiannong Quan (Journal of Meteorological Research, 2021)

Summertime surface energy balance fluxes at two Beijing sites - Junxia Dou; Sue Grimmond; Zhigang Cheng; Shiguang Miao; Dongying Feng; Mingshui Liao (International Journal of Climatology, 2019)
Summertime (June–August 2015) radiative and turbulent heat fluxes were measured concurrently at two sites (urban and suburban) in Beijing. The urban site has slightly lower incoming and outgoing shortwave radiation, lower atmospheric transmissivity and a lower surface albedo than the suburban site. Both sites receive similar incoming longwave radiation. Although the suburban site had larger daytime outgoing longwave radiation ( L ↑ ), differences in the daily mean L ↑ values are small, as the urban site has higher nocturnal L ↑ . Overall, both the midday and daily mean net all‐wave radiation ( Q * ) for the two sites are nearly equal. However, there are significant differences between the sites in the surface energy partitioning. The urban site has smaller turbulent sensible heat ( Q H ) (21–25% of Q * [midday–daily]) and latent heat ( Q E ) fluxes (21–45% of Q * ). Whereas, the suburban proportions of Q * are Q H 32–32% and Q E 39–66%. The daily (midday) mean Bowen ratio ( Q H / Q E ) was 0.56 and 0.49 (0.98 and 0.83) for the urban and suburban sites, respectively. These values are low compared with other urban and suburban areas with similar or larger fractions of vegetated cover. Likely, these are caused by the widespread external water use for road cleaning/wetting, greenbelts, and air conditioners. Our suburban site has quite different land cover to most previous suburban studies as crop irrigation supplements rainfall. These results are important in enhancing our understanding of surface–atmosphere energy exchanges in Chinese cities and can aid the development and evaluation of urban climate models and inform urban planning strategies in the context of rapid global urbanization and climate change.